Visualization of human C4b-binding protein and its complexes with vitamin K-dependent protein S and complement protein C4b. - Dahlbäck, B (1983)
C4b-binding protein (C4bp) participates in the regulation of the C3 convertase of the classical pathway of complement. By binding to C4b, which is one of the structural subunits of this enzyme, C4bp accelerates the decay-dissociation of the enzyme and renders C4b susceptible to degradation by factor I (C3b inactivator). C4bp is a high molecular weight plasma protein (Mr = 570,000) composed of apparently identical subunits (Mr = 70,000) linked by disulfide bonds. In plasma and in purified form C4bp also forms a bimolecular complex (Kd = 0.9 X 10(-7) M) with protein S, a recently identified vitamin K-dependent plasma protein. The binding sites on C4bp for protein S and C4b are distinct and noncompetitive and protein S does not influence the function of C4bp as a regulator of the C3 convertase. C4bp, C4b, and protein S were visualized by electron microscopy by negative staining. C4bp was found to have an unusual spider-like structure. It is composed of seven thin (30 A), elongated (330 A), and flexible subunits that are linked to a small central body. Protein S exhibited two globular domains of equal size with a center-to-center distance of approximately equal to 50 A. Protein S was found to bind to the C4bp through only one of its domains by attaching to a short subunit that is distinct from the other seven subunits. C4b imaged as an irregular, relatively compact molecule. It was found to interact with the peripheral ends of the elongated subunits, suggesting seven C4b-binding sites per molecule of C4bp.